An oomycete plant pathogen reprograms host pre-mRNA splicing to subvert immunity - Jie Huang (Nature Portfolio, 2017)
Various effectors of plant pathogens modulate host cell biology. Here, Huang et al. show PsAvr3c, an avirulence effector from oomycete plant pathogen Phytophthora sojae, can reprogram host pre-mRNA splicing for immune modulation.